Deciphering the profiles of grapevine microbiomes from rhizosphere-to-leaf compartments using multi-omic analysis - Wang, Bo; Wang, Zhuangwei; Chen, Zhenxiao; Zhang, Jing; Wang, Xicheng (Frontiers in Plant Science, 2026)
IntroductionRoot- and leaf-associated microbiomes are crucial for plant health and influence the yield and quality of the products. The composition of microbes and their association with the host depend on different factors that must be continuously investigated.ResultsWe examined the composition and structure of bacterial and fungal communities in four compartments (root, rhizoplane, rhizosphere, and leaf endosphere) of two grapevine varieties (‘Alachua’ and ‘Noble’) targeting the 16S rRNA V5–V7 and ITS regions.Results and discussionA comparison of the effects of the varieties and compartments showed that they were the major factors contributing to variations in the microbial structures. Bacterial alpha diversity significantly decreased from the rhizosphere to leaf endosphere, while the fungal alpha diversity did not show linear variations. According to normalized stochastic ratio analysis, deterministic processes dominated the bacterial and fungal assemblies of the leaf endosphere while stochastic processes in the rhizosphere and rhizoplane dominated the microbial assemblies. Assembly processes in bacterial and fungal roots differed (stochastic processes in bacteria and deterministic processes in fungi). Twenty shared core operational taxonomic units (OTUs) (bacteria, 13; fungi, 7) were identified across all compartments. Various stilbene compounds in leaf were significantly correlated with these shared core microbes, and weighted gene co-expression network analysis revealed that some hub genes were correlated with these metabolites. Thus, their role as regulators of grapevine microbiome interactions needs to be further evaluated. This study provided new profiles of the microbiota in different grapevines compartments, which suggested their association with grape metabolites and plant genes, representing a major development for further studies focused in understanding the role of these microorganisms for grapevine production.